Octocorallia (Cnidaria: Anthozoa) da plataforma continental e ilhas oceânicas brasileiras: famílias Paramuriceidae e Plexauridae - Medeiros, Marcelo Semeraro de (1998)
Fourteen species of octocorals, from the Brazilian continental platform and oceanic islands, from depths between 20 and 400m, were studied regarding aspects of their taxonomy, bathymetry, and geographical distribution. These species included nine Paramuriceidae (Bebryce cinerea, Bebryce sp., Heterogorgia uatumani, Muriceides hirtus, Muriceides aequatoriales, Muriceides sp., Placogorgia atlantica, Scleracis guadalupensis, and Villogorgia nigrescens) and five Plexauridae (Muricea atlantica, Muricea flamma, Muricea laxa, Muricea midas, and Muriceopsis sp. ). Among the species identified only at the rank of genus, it was demonstrated that Muriceopsis sp. is a species yet to be properly described in nomenclatural terms. Villogorgia was recorded for the first time in Brazilian waters and the geographical limits of five other species were changed (B. cinerea, H. uatumani, P. atlantica, S. guadalupensis and M. flamma). H. uatumani, S. guadalupensis, and V. nigrescens had their species global bathymetric range widened. Only two of the species here recorded were endemic to Brazil (M. flamma and M. aequatoriales). Biogeographical hipothesis from different authors were discussed, and it was shown that those based on material from very shallow waters (< 20m) were not adequate to characterize the distribution of octocoral species here reported.